Gender Identity Predicts Autobiographical Memory Phenomenology. Issue 4 (3rd May 2016) - Grysman, Azriel; Fivush, Robyn
Summary: Gender differences emerge regularly in autobiographical memory research. We suggest that gender differences in phenomenological self‐report measures of autobiographical memory are rooted in gender identity rather than categorical gender. Reminiscing about the past is perceived as a female‐typical activity, and therefore, gender‐typical individuals will conform to these stereotypes. In this study, 196 participants, age 18–40, each rated the phenomenology of four event memories. Ratings of feminine gender identity, also completed by participants, consistently correlated with MEQ scores, indicating that greater endorsement of feminine gender norms predicted higher memory quality and valence. Masculine gender identity also correlated with MEQ scores, but these correlations were less consistent. Findings suggest that a focus on gender identity can both explain the source of some gender differences in autobiographical memory and potentially explain some inconsistencies in the current literature.Copyright © 2016 John Wiley & Sons, Ltd.